Addition of Funds by Merchants in Payments Through The QRIS from an Islamic Law Perspective - Putri, Feiza Alevia (Universitas Negeri Semarang, 2025)
The practice of adding funds for consumers who make transactions using QRIS is implemented by merchants to avoid profits from administrative fees or Merchant Discount Rates. The mechanism for disbursing funds from PJP to merchants and the form of additional funds are laden with elements of usury. Therefore, the objective of this study is to identify the financial management mechanisms for fund additions by merchants in QRIS payments and to analyze the legal implications of fund additions by merchants in QRIS payments from an Islamic legal perspective. The research method used is qualitative research with a legal-empirical approach. The data collected consists of primary and secondary data, with data collection techniques including literature review, interviews, observation, and documentation. Based on the research findings, it can be stated that the additional funds are not listed on the transaction receipt but are instead communicated verbally or displayed in the corner of the QRIS printout. Consumers scan the QR code using their digital wallet platform, then enter the total amount themselves, and verify the transaction. After that, a notification appears stating that the funds have been received by the merchant. However, the disbursement of funds from the PJP to the merchant's account takes up to H+1 calendar days. Additionally, the addition of funds by merchants in QRIS payments contains elements of usury, rendering the transaction fasid. The additional funds charged by merchants to consumers constitute unlawful income if both parties do not mutually consent. The addition of funds by the merchant in payments via QRIS can be considered as ujrah and valid if both parties mutually consent and agree. Furthermore, the delay in the transfer of funds from the PJP to the merchant's account constitutes riba nasiah.